ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN PEMILIHAN METODE KONTRASEPSI JANGKA PANJANG (MKJP) PADA AKSEPTOR KB WANITA DI KECAMATAN BANYUBIRU KABUPATEN SEMARANG (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2015)
One of The National Medium Term Development Plan 2010-2014 indicator is to increase active acceptors of long-term contraceptive method. In Banyubiru subdistrict, the proportion of long-term contraceptive method are low (22,03%). The purpose of this research is to analysed the factors associated preference of long-term contraceptive method among women contraception acceptors in Banyubiru subdistrict. This research was an explanatory research with cross sectional approach. The population were all women of contraception acceptors in Banyubiru subdistrict. The sample were 104 women, used simple random sampling. This research used quisionaire instrument and analyze used chi square test (Î±=0,05). The result showed that variables which associated preference of long-term contraceptive method are educational level (sig=0,015), knowledge (sig=0,001), support of spouse (sig=0,002), culture (sig=0,004), level of well-being (sig=0,034), communication, information, and education of contraception (sig=0,018). As for age (sig=0,127) and number of children (sig=0,529) were not associated with preference of long-term contraceptive method. Suggestion for KB department in district and subdistrict are planning surveilance program of long-term contraceptive method and increasing the service quality by giving counseling and more information.